HEDONIC SHOPPING DAN FLASH DISCOUNT TERHADAP IMPULSE BUYING DENGAN POSITIVE EMOTION SEBAGAI VARIABEL MEDIASI - Haryanti, Intisari Sari; Dessyarti, Robby Sandhi; Pratiwi, Aliah; Nurulrahmatiah, Nafisah; Aryani, Feni (Universitas Riau Kepulauan, 2025)
This study aims to analyze the influence of hedonic shopping and flash discount on impulse buying, with positive emotion as a mediating variable among e-commerce consumers. To achieve this objective, a quantitative approach was employed using a survey method, where data were collected through online questionnaires distributed to 200 respondents who had previously made impulse purchases during flash discount programs. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the relationships among the variables in the research model. The results show that hedonic shopping has a direct effect on impulse buying with a path coefficient of 0.198, while flash discount exhibits a stronger direct effect with a coefficient of 0.482. Both independent variables also significantly influence positive emotion, with hedonic shopping showing a coefficient of 0.399 and flash discount a higher coefficient of 0.487. Positive emotion itself has a significant positive effect on impulse buying with a coefficient of 0.319. The R² value for positive emotion is 0.667, and for impulse buying it is 0.834, indicating that the model explains 83.4% of the variance in impulse buying behavior. These findings confirm that both hedonic shopping and flash discount play important roles in driving impulse buying, either directly or through the mediation of positive emotion. The practical implication is that e-commerce companies should pay attention to consumers’ emotional experiences when designing promotional strategies and shopping experiences